Deferasirox in iron-overloaded patients with transfusion-dependent myelodysplastic syndromes: Results from the large 1-year EPIC study - Gattermann,N. (Elsevier Limited, 2015)
The prospective 1-year EPIC study enrolled 341 patients with myelodysplastic syndromes (MDS); although baseline iron burden was >2500. ng/mL, ∼50% were chelation-naïve. Overall median serum ferritin decreased significantly at 1 year (p=0.002). Decreases occurred irrespective of whether patients were chelation-naïve or previously chelated; changes were dependent on dose adjustments and ongoing iron intake. Sustained reductions in labile plasma iron were observed. Discontinuation rate (48.7%) and adverse event profile were consistent with previously reported deferasirox data in MDS. Alanine aminotransferase levels decreased significantly; change correlated significantly with reduction in serum ferritin (p<0.0001). This large dataset prospectively confirms the efficacy and well characterizes the safety profile of deferasirox in MDS. © 2010 Elsevier Ltd.